First full cool down of the SPIRAL 2 superconducting LINAC. (September 2020) - Ghribi, Adnan; Aburas, Muhammad; Baumont, Yoann; Bernaudin, Pierre-Emmanuel; Bonneau, Stéphane; Duteil, Guillaume; Ferdinand, Robin; Lechartier, Michel; Leyge, Jean-François; Lescalié, Guillaume; Thivel, Yann; Trudel, Arnaud; et al.
Highlights: First full cool down of the SPIRAL 2 superconducting linear accelerator. Cool down requirements methods and procedures as well as actual data. Preparing the operation mode through experimental run. New multidisciplinary challenges between cryogenic and RF for superconducting accelerator. Abstract: SPIRAL 2 is a high intensity heavy ions beams accelerator project that has been going on for more than 10 years now. Countless efforts in different disciplines made it what it is today. One of the most important steps after the set up of the different equipments has been the very first full cool down of the superconducting cavities in an accelerator operation type configuration. While this has been a major achievement for the SPIRAL 2 teams, it also hi-lighted new challenges and constraints that would have to be addressed in order to have a high availability rate of the beam from the cryogenics side. This paper retraces this particular episode.